Job Insecurity On Turnover Intention In Banjarmasin City Public Health Centers: A Systematic Literature Review - Meiske Claudia; Muhammad Ary Aprian Noor (Lembaga Pengembangan Kinerja Dosen, 2024)
Job insecurity is a major concern among employees in various organizations, including public health centers in Banjarmasin City, Indonesia. A systematic literature review was conducted to investigate the influence of job insecurity on turnover intention among community health center employees in Banjarmasin. The results of the analysis carried out on 14 articles showed that job insecurity had a positive effect on turnover intention. Job insecurity can lead to stress, anxiety, and dissatisfaction, which can negatively impact an employee's commitment to their organization and increase their intention to leave. All studies used quantitative research methods with survey techniques for data collection. Strategies to enhance job security perceptions, such as improving communication transparency, offering career development opportunities, and implementing fair and consistent human resource practices, may help mitigate turnover intentions. The findings of the studies highlight the importance of addressing job insecurity to reduce turnover intention and improve employee retention in primary health care in Banjarmasin. Investing in initiatives that cultivate a sense of job security and stability among health workers can contribute to the long-term sustainability and effectiveness of primary healthcare service delivery in the region.